2015
DOI: 10.1007/s00441-015-2273-x
|View full text |Cite
|
Sign up to set email alerts
|

A population of mitochondrion-rich cells in the pars recta of mouse kidney

Abstract: Following perfusion of adult mouse kidney with a solution of nitroblue tetrazolium (NBT), certain epithelial cells in the pars recta (S3) segments of proximal tubules react to form cytoplasmic deposits of blue diformazan particles. Such cells are characterized by dark cytoplasm, small and often elliptical nuclei, elaborate, process-bearing profiles, and abundant mitochondria. The atypical epithelial cells display the additional characteristic of immunoreactivity for a wide spectrum of antigens, including mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The 1 st sub-cluster were not dying cells as the median number of genes and transcripts were higher than cluster 1, so we hypothesize that they belong to this poorly characterized cell type ( Supplementary Fig. 2f-g) 18 . The 2 nd sub-cluster marked parietal epithelial cells (PECs) (CL_1000452) lining the Bowman's capsule, which are known to specifically express VCAM1 19 .…”
Section: Proximal Tubule Epithelial Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…The 1 st sub-cluster were not dying cells as the median number of genes and transcripts were higher than cluster 1, so we hypothesize that they belong to this poorly characterized cell type ( Supplementary Fig. 2f-g) 18 . The 2 nd sub-cluster marked parietal epithelial cells (PECs) (CL_1000452) lining the Bowman's capsule, which are known to specifically express VCAM1 19 .…”
Section: Proximal Tubule Epithelial Cellsmentioning
confidence: 91%
“…2a-d). PT cells in general and a subset of mouse S3 PT cells have been described to be especially abundant in mitochondria 18 . The 1 st sub-cluster were not dying cells as the median number of genes and transcripts were higher than cluster 1, so we hypothesize that they belong to this poorly characterized cell type ( Supplementary Fig.…”
Section: Proximal Tubule Epithelial Cellsmentioning
confidence: 99%
“…After surgery, the contralateral UUO‐NOKs experience compensatory growth with little structural change 43 . Meanwhile, UUO‐OKs exhibit rapid loss of proximal tubular mass at 7dUUO followed by severe atrophy at 14dUUO 43 . Additionally, in UUO‐OKs, renal blood flow and oxygen tension decrease in both cortical (since 4hUUO) and medullary (since 8hUUO) sections, 18 which has been hypothesized to have significant effects on substrates' availability and energy metabolism, mainly in UUO‐OKs.…”
Section: Mitochondrial Dysfunction In the Uuo Modelmentioning
confidence: 99%
“…Recently it was reported that cells morphologically similar to human PTPCs were found in the S3 segment, pars recta, in male mice. 15 The cells were characterized by positive staining for vimentin, but in contrast to human PTPCs the cells had abundant mitochondria. These mitochondrion high cells transiently increased in numbers following UUO, but were subsequently lost, due to atrophy after a few days.…”
Section: Discussionmentioning
confidence: 94%